Research participation among state and local public health emergency preparedness and response programs. (June 2018) - Yusuf, H.; Ekperi, L.; Groseclose, S.; Siegfried, A.; Meit, M.; Carbone, E.
Abstract: Objectives: The objective of our study was to assess whether state and local health staff participated in public health emergency preparedness research activities and what partner organizations they collaborated with on research. Study design: This is a cross-sectional study. Methods: Data were derived from a 2014 web-based survey of state, territorial, and local health departments conducted by the Centers for Disease Control and Prevention and NORC at the University of Chicago as part of a larger project to assess the public health emergency preparedness and response research priorities of state and local health departments. Results: Overall, 30% of survey respondents indicated that health department staff were involved in public health preparedness and response research-related activities. Thirty-four percent indicated that they were extremely or moderately familiar with emergency preparedness research and literature. Approximately 67% of respondents reported interest in receiving additional information and/or training related to the preparedness research and literature. The most frequently reported partners for collaboration in preparedness research–related activities were schools of public health (34%). Conclusions: Our findings suggest that there is health department interest in learning more about preparedness and response science and that additional efforts are needed to increase health department participation in public health emergency preparedness and response research-related activities. Highlights: Only 30% of health departments reported having staff involved in preparedness research. Survey respondents were not very familiar with preparedness research. Majority of respondents indicated interest in research information and training. Health department research collaborations were most often with schools of public health.